Obtaining Isocyanates Through Thermal Decomposition of Carbamates - Muxabbat Sattarovna Khatamova; Sevara Gulmirzayevna Dosimbetova (Scientific Trends, 2025)
In this article, methods of synthesizing isocyanates through the thermal decomposition of carbamate compounds have been studied. The research focuses on the structure of various carbamates and their decomposition mechanisms under the influence of temperature. Additionally, the high reactivity of isocyanates and their industrial significance (for example, in the production of polyurethanes) are substantiated. Conditions of thermal decomposition, factors affecting the reaction (temperature, catalysts, pressure), and the analysis of the resulting products are presented. Based on the obtained results, the possibilities of obtaining isocyanates in an environmentally and economically efficient way are analyzed.
Keywords: carbamates, thermal decomposition, isocyanates, reactivity, polyurethanes, catalysts, temperature, pressure, environmental efficiency, industrial chemistry